Material politics : disputes along the pipeline - Barry, Andrew, 1960- (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
"Presents an original theoretical approach to political geography by revealing the paradoxical relationship between materials and politics"--
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Geopolitics; Materials -- Political aspects; Material culture -- Political aspects; Petroleum pipelines -- Political aspects; International economic relations -- Political aspects; SCIENCE -- Earth Sciences -- Geography; Electronic books